Particle-ladened flow in pipes and channels - Syafiq Hazman Zakariah (2015)
This project is a research-based project between Nanyang Technological University and Jurong Port Private Limited. The first aim of this project is to experimentally investigate the air and cement flow encountered in an air-slide conveyor and pneumatic conveyor. Said conveyors are presently used at Jurong Port Terminal. The second aim is to, based on the results of the investigations, explore potential engineering modifications that can increase cement delivery rate or reduce instances of choking e.g. varying the mass flow rate (cement) by adjusting the speed of the blower. These modifications are targeted to increase the operational efficiency of cement rig.